Indivisible : how to forge our differences into a stronger future - Hamilton, Denise (Countryman Press, an imprint of W.W. Norton & Company, 2024)
"Denise Hamilton has always believed in the power and promise of a word she learned as a schoolgirl: "indivisible." In her groundbreaking debut, she challenges readers to move beyond current notions of diversity and inclusion to build communities, workplaces, and relationships that live up to that word. She urges us to reexamine long-held beliefs and habits and to dismantle hierarchies that shape our current society. If we want to repair the fraying stitches that bind us together, if we want to build a truly close-knit collective, we cannot settle for our present approach. It's time to recalibrate and identify a goal higher than inclusivity-the goal of indivisibility. As a nationally recognized DEI leader, Hamilton shares accessible, personal stories and offers self-examination questions, intentional action steps, and journal prompts. While the book has a focus on business and leadership, the lessons within can transform our professional and personal lives"--